Site selection and system sizing of desalination plants powered with renewable energy sources based on a web-GIS platform. Issue 3 (9th August 2021) - Koutroulis, Eftichios; Petrakis, George; Agou, Vicky; Malisovas, Athanassios; Hristopulos, Dionissios; Partsinevelos, Panagiotis; Tripolitsiotis, Achilleas; Halouani, Nabila; Ailliot, Pierre; Boutigny, Marrie; Monbet, Valerie; Allard, Denis; et al.
Abstract : Purpose: The combination of desalination technology with renewable energy sources (RES) provides a sustainable approach for increasing potable water availability without imposing negative environmental effects. This paper aims to present the development of a platform, which is an internet-based tool integrating the design optimization of desalination systems with spatial modeling based on a geographic information system (GIS). Design/methodology/approach: The proposed platform assists decision-makers to select the optimal location and configuration of both the energy- and water-related subsystems of desalination plants that are power-supplied by RES, such that the lifetime cost of the overall desalination plant is minimized. It enables to optimize the desalination plant site selection and sizing with various hybrid power supply (solar, wind, wave and electrical grid power systems) and desalination technologies combinations, while simultaneously exploiting spatial technologies in an internet-based GIS platform. Findings: A pilot study for the optimal design of stand-alone and grid-connected desalination plants powered by RES is presented, which demonstrates the functionality and features of the proposed platform. It is also shown that a grid-connected desalination plant designed by the proposed software design tool exhibits significantly lower lifetime installation and maintenance costs compared to its stand-alone counterpart. Originality/value: The proposed platform combines technological, scientific and industrial knowledge with information about societal/political conditions and geo-spatial technologies in a user-friendly graphical interface. Therefore, it provides a design tool enabling its users to secure water supply in a sustainable and economically viable manner.